The mouse 5HT5 receptor reveals a remarkable heterogeneity within the 5HT1D receptor family. - Plassat, J L (1992)
Serotonin (5-HT) is a neuromodulator that mediates a wide range of physiological functions by activating multiple receptors. Using a strategy based on amino acid sequence homology between 5-HT receptors that interact with G proteins, we have isolated a cDNA encoding a new serotonin receptor from a mouse brain library. Amino acid sequence comparisons revealed that this receptor was a distant relative of all previously identified 5-HT receptors; we therefore named it 5HT5. When expressed in Cos-7 cells and NIH-3T3 cells, the 5HT5 receptor displayed a high affinity for the serotonergic radioligand [125I]LSD. Surprisingly, its pharmacological profile resembled that of the 5HT1D receptor, which is a 5-HT receptor subtype which has been shown to inhibit adenylate cyclase and which is predominantly expressed in basal ganglia. However, unlike 5HT1D receptors, the 5HT5 receptor did not inhibit adenylate cyclase and its mRNA was not found in basal ganglia. On the contrary, in situ hybridization experiments revealed that the 5HT5 mRNA was expressed predominantly in cerebral cortex, hippocampus, habenula, olfactory bulb and granular layer of the cerebellum. Our results therefore demonstrate that the 5HT1D receptors constitute a heterogeneous family of receptors with distinct intracellular signalling properties and expression patterns.